Teacher and parent perspectives on extracurricular activities for students with intellectual and developmental disabilities - Cain, Irina; Bruno, Lauren; Agran, M.; Wojcik, Andrew; Achola, Edwin; Thoma, Colleen; Nixon, Cynthia; Tamura, Ronald (Inclusion, 2025)
Keywords: Extracurricular activity; Intellectual disability; Qualitative research; Semi-structured interview; dept.sed

Introduction to the special section on drivers with ASD - Volkmar, Fred (Journal of Autism and Developmental Disorders, 2025)
Keywords: Autism; Clinical psychology; Computer science; Developmental psychology; Engineering; Engineering physics; Medicine; Psychology; Public health; Section (typography); Special section; dept.sed

Considering emerging, complementary, and alternative treatments - Øien, Roald; Nordahl‐Hansen, Anders; Skarbek, Sacha; Tolkin, Samuel; Volkmar, Fred (Handbook of Evidence-Based Practices in Autism Spectrum Disorder, 2025)
Keywords: Computer science; dept.sed

Evidence-based practices in autism: where we started to where we are now - Reichow, Brian; Doehring, Peter; Volkmar, Fred (Handbook of Evidence-Based Practices in Autism Spectrum Disorder, 2025)
Keywords: Autism; Developmental psychology; Psychology; dept.sed

Evidence-based practices and treatments in autism spectrum disorder: concluding thoughts - Volkmar, Fred; Doehring, Peter; Reichow, Brian (Handbook of Evidence-Based Practices in Autism Spectrum Disorder, 2025)
Keywords: Autism; Autism spectrum disorder; Cognitive psychology; Developmental psychology; Physics; Psychology; Spectrum (functional analysis); dept.sed

AI in Special Education: Bridging Gaps, Easing Workloads, and Inspiring Inclusion - DiBattista, Eileen; Erazmus, Kelly; Tucker, Lauren (Teaching Exceptional Children, 2025)
Keywords: Bridging (networking); Inclusion (mineral); Learning disability; Special education; Teaching method; dept.sed

From Theory to Practice: A Tiered Support Model for Increasing Preservice Teachers’ Use of Behavior Specific Praise - Hynes, Kristy; Gershwin, Tracy (Journal of Educational and Psychological Consultation, 2025)
Keywords: Praise; Qualitative research; Work (physics); dept.sed

Assistive Technology Multi-Tiered System of Supports (AT-MTSS): Improving AT Delivery - McMahon, Don; Tucker, Lauren (Journal of Special Education Technology, 2025)
Keywords: Assistive technology; CLARITY; Inclusion (mineral); Psychological intervention; Special education; Special needs; Universal Design for Learning; Variety (cybernetics); accessibility; assistive technology; dept.sed; multi-tiered systems of supports; special education teacher preparation; universal design for learning

Self-Monitoring to Reduce Student Distraction in Higher Education - Brahm, Meghan; Hynes, Kristy (College Teaching, 2025)
Keywords: Applied behavior analysis; Cognitive psychology; Distraction; Higher education; Mathematics education; Pedagogy; Political science; Psychology; Student engagement; classroom distraction; dept.sed; higher education; self-monitoring; student engagement

Considering emerging, complementary, and alternative treatments - Øien, R.A.; Nordahl-Hansen, A.; Skarbek, S.; Tolkin, S.; Volkmar, F.R. (Handbook of Evidence-Based Practices in Autism Spectrum Disorder, 2025)
The chapter “Considering Emerging Complementary and Alternative Treatments“delves into the diverse landscape of non-mainstream interventions for autism spectrum disorder (ASD). The discourse navigates through the historical evolution, current status, and future prospects of complementary and alternative medicine treatments. The narrative acknowledges the dichotomy between scientifically validated practices and those emerging from anecdotal and preliminary evidence. Key topics include vitamin and mineral supplementation, dietary interventions, secretin administration, chelation therapy, neurofeedback, sensory-based therapies, and facilitated communication. Each treatment is critically evaluated for its empirical support, safety, and clinical utility. The chapter emphasizes the necessity for rigorous research methodologies and balanced clinical perspectives in assessing these interventions. By providing a comprehensive overview, it aims to inform clinicians, researchers, and caregivers about the potential benefits and pitfalls of CAM treatments, fostering informed decision making in the therapeutic management of ASD. © Springer Nature Switzerland AG 2025.
Keywords: Alternative treatments; Complementary and alternative medicine; Complementary treatments; Emerging treatments; dept.sed

The evolution of evidence-based practice guidelines in autism spectrum disorder: how can these begin to support individualized, community-based practices? - Doehring, P.; Reichow, B.; Volkmar, F.R. (Handbook of Evidence-Based Practices in Autism Spectrum Disorder, 2025)
Evidence-based practice guidelines use specific rubrics to first evaluate the quality of individual outcome research studies and then the overall strength of the evidence, ultimately generating recommendations for clinical and educational practice. This chapter reviews the methodologies used across three different types of guidelines spanning health and education, by comparing recommendations related to practices for addressing sleep problems. The review reveals that these guidelines share many features, with some differences suggesting areas of improvement. More fundamental differences between biomedical and psychosocial practices, as well as specific challenges of community-based practices, suggest other opportunities for improvement in the design of outcome research and in the development of practice guidelines. This chapter concludes by discussing how to close other gaps in guideline development by emphasizing focused practices instead of comprehensive treatment programs (CTPs), integrating research findings from related populations, developing recommendations for program and policy leaders, and imagining reviews that potentially offer more individualized recommendations. © Springer Nature Switzerland AG 2025.
Keywords: Autism spectrum disorder; Evidence-based practice; Outcome studies; Professional practice guidelines; Systematic research reviews; dept.sed

Evidence-based practices and treatments in autism spectrum disorder: concluding thoughts - Volkmar, F.R.; Doehring, P.; Reichow, B. (Handbook of Evidence-Based Practices in Autism Spectrum Disorder, 2025)
This concluding chapter summarizes how the field has advanced, the current state of evidence-based practices, unique insights derived from systematic reviews of practices and programs, and directions for the future. We note major gains since the first attempts in the early 1990s to provide information on evidence-based practices, including more sophisticated research methods for meta-analytic studies and systematic reviews. The emergence of very high-quality reviews of rigorous outcome research over the past 15 years has accelerated interest in evidence-based practices. At the same time, controversies surrounding questions of research design, study selection, the potential bias relative to cultural and racial factors, persistent gaps in research on adults and those with more significant levels of disability, and other areas remain to be addressed. We note some area of active discussion, e.g., relative to whether or not to screen and the need to help community-based professionals responsible for tailoring evidence-based practices to the many different individuals and settings they serve. If we are able to reconcile the researcher’s desire for experimental rigor with the flexibility required for outcome studies conducted in community-based settings, we might begin to demonstrate the kinds of population impacts needed to justify more substantial funding and policy changes. Several areas of additional research are outlined. © Springer Nature Switzerland AG 2025.
Keywords: Eclectic programs; Evidence-based treatment; Future directions; Meta-analyses; Systematic reviews; dept.sed

Handbook of Evidence-Based Practices in Autism Spectrum Disorder - Reichow, B.; Doehring, P.; Volkmar, F.R. (2025)
The handbook examines the empirical status of interventions and treatments for individuals with autism spectrum disorder (ASD). It offers an insightful and balanced perspective on topics ranging from the historical underpinnings of autism treatment to the use of psychopharmacology and the implementation of EBPs. The book reviews the conceptualization of evidence-based practices (EBPs) as well as considerations for implementing such practices across settings. In addition, it describes emerging treatments – though they cannot yet be considered evidence-based – that have produced limited but highly promising results. The book also describes treatments and therapies that have been proved ineffective. It explores ways in which EBPs can be applied in inclusive school settings, pedatric settings, in-patient treatment progams, and college-based programs for transition-aged youth. The volume describes outcomes from the development of EBP guidelines at the national level (in Scotland) and, more broadly, in the United States and outlines how such guidelines can be adapted to offer more individualized intervention. Key areas of coverage include: Comprehensive treatment models, including early intensive behavioral intervention, pivotal response treatment, Early Start Denver Model, and Naturalistic Developmental Behavioral Interventions. Focal treatments addressing the core deficits of ASD and its co-occuring conditions. Social skills, communication, and the use of applied behavior analysis (ABA) practices for teaching new skills and decreasing challenging behaviors. Sensory-based interventions, psychopharmacology, cognitive behavior therapy, and parent education programs (e. g., Project ImPACT). The Handbook of Evidence-Based Practices in Autism Spectrum Disorder is an invaluable resource for researchers, professors, and graduate students as well as clinicians, therapists, and all professionals working in the fields of developmental, clinical child, and school psychology, pediatrics, social work, behavior analysis, allied health sciences, public health, child and adolescent psychiatry, early childhood intervention, and general and special education. © Springer Nature Switzerland AG 2025.
Pages: 537
Keywords: ASD; Adaptive and challenging behaviors and autism; Augmentative and assistive technology and ASD; Autism treatment; Behavioral-developmental interventions and ASD; Cognitive-behavioral therapy (CBT) and autism; Communication deficits and autism; Controversial therapies and autism; Early Intensive Behavioral Intervention (EIBI); Early Start Denver Model (ESDM) and ASD; JASPER and autism spectrum disorder treatment; Parent education and support programs and ASD; Pivotal Response Treatment (PRT) and autism; Project ImPACT and autism spectrum disorder; Psychopharmacology and autism; Sensory-based interventions and autism; Sleep and autism spectrum disorder; Social skills training and autism; Socioeconomic status and autism treatments; TEACCH® Autism Program; The SCERTS® Model; community settings; dept.sed; medical

Evidence-based practices in autism: where we started to where we are now - Reichow, B.; Doehring, P.; Volkmar, F.R. (Handbook of Evidence-Based Practices in Autism Spectrum Disorder, 2025)
When we published our first volume, the evidence-based practice (EBP) movement in the field of autism spectrum disorder (ASD) had already begun to gain strength around the world, and it has since shown no signs of abating. Multiple organizations and groups have now produced EBP guidelines concerning the treatment and/or identification of ASD. However, the resulting definitions continue to vary in important ways across professions and sometimes even within their subdivisions. A universal definition of EBP remains elusive. While these conclusions drawn from the previous edition of this book still hold true, we are nonetheless encouraged by the growth in interest in EBP and by the dramatic increase in the number of high-quality research studies over the past 15 years and so are excited to offer this updated and expanded handbook. This chapter serves as an introduction to the current state of affairs with respect to evidence-based practices in autism spectrum disorders. © Springer Nature Switzerland AG 2025.
Keywords: Evidence-based practice; History; Intervention; Practice guidelines; Treatment; dept.sed

Building TRUST: Empowering Teachers to Support Students With Emotional and Behavioral Disorders - Mitchell, Carolyn; Gershwin, Tracy; Robinson, Jason; Hynes, Kristy (Intervention in School and Clinic, 2025)
Keywords: Applied psychology; Developmental psychology; Emotional and behavioral disorders; Learning disability; Mathematics education; Pedagogy; Psychology; Reading (process); Special education; dept.sed; peer-reviewed

Relationships Matter: The Art of Creating Meaningful Interactions With Students - Hynes, Kristy; Gershwin, Tracy; Robinson, Jason; Mitchell, Chrissa (Beyond Behavior, 2025)
Keywords: Foundation (evidence); Mathematics education; Pedagogy; Psychological intervention; Psychology; dept.sed; peer-reviewed